Mutational profiles of Brenner tumors show distinctive features uncoupling urothelial carcinomas and ovarian carcinoma with transitional cell histology - Pfarr, Nicole; Leichsenring, Jonas; Penzel, Roland; Endris, Volker; Schirmacher, Peter; Stenzinger, Albrecht (Genes, chromosomes & cancer, 2017)
Brenner tumors (BT) are rare ovarian tumors encompassing benign, borderline, and malignant variants. While the histopathology of BTs and their clinical course is well described, little is known about the underlying genetic defects. We employed targeted next generation sequencing to analyze the mutational landscape in a cohort of 23 BT cases (17 benign, 2 borderline, and 4 malignant) and 3 ovarian carcinomas with transitional cell histology (TCC). Copy number variations (CNV) were validated by fluorescence in-situ hybridization (FISH) and quantitative PCR-based copy number assays. Additionally, we analyzed the TERT promotor region by conventional Sanger sequencing. We identified 25 different point mutations in 23 of the analyzed genes in BTs and 10 mutations in 8 genes in TCCs. About 57% percent of mutations occurred in genes involved in cell cycle control, DNA repair, and epigenetic regulation processes. All TCC cases harbored TP53 mutations whereas all BTs were negative and none of the mutations observed in BTs were present in TCCs. CNV analysis revealed recurrent MDM2 amplifications in 3 out of 4 of the malignant BT cases with one case harboring a concomitant amplification of CCND1. No mutations were observed in the TERT promoter region in BTs and TCCs, which is mutated in about 50%-75% of urothelial carcinoma and in 16% of ovarian clear-cell carcinomas. In conclusion, our study highlights distinct genetic features of BTs, and detection of the triplet phenotype MDM2 amplification/TP53 wt/TERT wt may aid diagnosis of malignant BT in difficult cases. Moreover, selected genetic lesions may be clinically exploitable in a metastatic setting.
Gesehen am 20.09.2018